NEW RUGOSE CORALS FROM THE UPPER SILURIAN OF THE WESTERN BALKHASH REGION - Stolbova V.P. (My University, 2002)
Two new species, Calostylis propria and Calostylis variseptata, from the Akkan Horizon of Kazakhstan (western Balkhash Region) are described.
Keywords: Silurian; Paleozoic::Silurian; Палеозой::Силурийская